The Effects of Using the KNfun Model on Oral Health Knowledge and Behavior Among Parents; and on Dental Plaque Among Preschool Children - Manratoh, Suraiya; Palanukunwong, Onchinee; Like, Yulithi (Journal of Nursing and Public Health Research, 2022)
The objectives of the one-group pretest-posttest design were to examine the effects of using the KNfun program on the oral health knowledge and behavior of parents and the dental plaque levels of preschool children in the Preschool Child Development Centers in Songkla province. Participants were 30 patients and preschool children in the Child Development Centers. The research instruments were the KNfun program, an oral health knowledge questionnaire, a toothbrushing skills assessment form, a plaque control record, and a baby bottle milk feeding record. The Index of Item-Objective Congruence of an oral health knowledge and a toothbrushing skills assessment form was between 0.67-1.00. The reliability of these questionnaires was 0.62. Data were analyzed using descriptive statistics and the paired sample t-test. The results showed that after using the KNfun program, the mean score of parents’ oral health knowledge and toothbrushing skills were significantly higher than before attending the program (p-value < 0.001). The plaque index score of children was significantly lower than before attending the program (p-value < 0.001). The rate of preschool children bringing a bottle of milk to the child development center dropped from 74.1 % to 0 %. Therefore, the KNfun program can reduce the risk of caries among preschool children. The KNfun program should be continued in order to address the prevalence of dental caries among preschool children.